Prediction of catalytic activity of Pt3Re1 alloy for C-C bond cleavage in the ethanol oxidation reaction (2016)
Design of catalysts able to cleave C-C bond in ethanol oxidation reaction at low temperatures is primordial for improving the direct ethanol proton exchange membrane fuel cells. Pt-Re alloy seems to be an appropriate material for C-C bond cleavage in ethanol decomposition, but yet, it has not been studied in-depth the reactivity of this alloy for this step. Then, in this work, the reactivity of Pt$_3$Re$_1$ surface for the C-C bond cleavage is studied and compared with reactivity of pure metal surfaces Pt(111) and Re(0001), using Density Functional Theory (DFT) and the descriptor based approach for catalyst design. Adsorption energy of CH, CO and CHCO are proposed as descriptors since they are the molecules involved in C-C bond cleavage of CHCO, which is considered the most likely reaction step for C-C bond cleavage in ethanol oxidation reaction. Consequently, the energetic and geometrical properties of the adsorption of these molecules on Pt, Re and Pt3Re1 are studied and analyzed respect to the electronic structure of the surface in order to understand the reactivity for C-C bond cleavage of the studied surfaces. It was found that the addition of Re to Pt leads to form active sites with Re atoms, which are more reactive for the C-C bond cleavage in CHCO, but the sites without Re are less reactive for this step. These findings suggest that despite higher ability to interact with carbon atoms of Re, the Re addition to Pt does not enhance significantly the C-C cleavage in ethanol oxidation reaction, since the higher reactivity of sites with Re atom in Pt3Re1 should not compensate the lower reactivity of the sites without Re.